2009
DOI: 10.1038/nbt.1516
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human embryonic stem cells with features of neoplastic progression

Abstract: Cultured human embryonic stem (hES) cells can acquire genetic and epigenetic changes that make them vulnerable to transformation. As hES cells with cancer-cell characteristics share properties with normal hES cells, such as self-renewal, teratoma formation and the expression of pluripotency markers, they may be misconstrued as superior hES cells with enhanced 'stemness'. We characterize two variant hES cell lines (v-hESC-1 and v-hESC-2) that express pluripotency markers at high levels and do not harbor chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
229
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(244 citation statements)
references
References 30 publications
12
229
2
1
Order By: Relevance
“…Indeed, using high-resolution CGH analysis, Hovatta et al (2010) found 71 genes deleted and 1471 duplicated in 'normal' hESC line H1 after less than 60 passages. It has also been reported that H9 has chromosomal abnormalities (Lefort et al 2008;Werbowetski-Ogilvie et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, using high-resolution CGH analysis, Hovatta et al (2010) found 71 genes deleted and 1471 duplicated in 'normal' hESC line H1 after less than 60 passages. It has also been reported that H9 has chromosomal abnormalities (Lefort et al 2008;Werbowetski-Ogilvie et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The McMaster University Animal Care Council approved all procedures and protocols. Undifferentiated hiPSCs (1.0 Â 10 6 cells per mouse) were mechanically collected, resuspended in PBS and then injected intratesticularly into male non-obese diabetic/severe combined immunodeficient (NOD/SCID) 28 . Mice were killed 8 weeks after initial injection.…”
Section: Methodsmentioning
confidence: 99%
“…The hESC line and Fibs-hiPSCs were cultured on Matrigel (BD Biosciences) in MEF-conditioned medium (MEF-CM) supplemented with 8 ng ml À 1 bFGF (Invitrogen) as previously described 28 . Fib hiPSCs and umbilical CB hiPSCs were cultured on irradiated feeder MEFs in DMEM/F12 (Gibco) with 20% Knockout Serum Replacement (Gibco), 100 mM b-mercaptoethanol, 100 mM nonessential amino acid (Gibco), 1 mM L-glutamine (Gibco) and 10 ng ml À 1 bFGF.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Navarro and colleagues have demonstrated that in mESC the three pluripotency factors (Nanog, Oct4 and Sox2) bind and repress Xist, the master regulator of X inactivation, but it is not clear how the trisomy of this chromosome could confer a proliferative or selective advantage to cells (Navarro et al, 2008). The gain of the entire or a part of chromosome 20 is an other typical chromosomal variation in hESCs (Rosler et al, 2004;Baker et al, 2007;Maitra et al, 2005;Spits et al, 2008;Lefort et al, 2008;Werbowetski-Ogilvie et al, 2009). It is known that the amplification of the region 20q11.2 is recurrent in many types of cancer (melanoma, Koynova et al, 2007;breast, Guan et al, 1996;lung, Tonon et al, 2005;bladder, Hurst et al, 2004) and the possible candidate genes that can increase cell proliferation, are BCL2L1, directly involved in cell death and proliferation, DNMT3B, important for the correct imprinting, and POFUT1, which is indispensable for NOTCH cascade signaling activation.…”
Section: Chromosome Variation In Human Primate and Rodent Escsmentioning
confidence: 99%